The Role of Executive Functions in Socioeconomic Attainment Gaps: Results From a Randomized Controlled Trial. Issue 5 (6th February 2020) - Blakey, Emma; Matthews, Danielle; Cragg, Lucy; Buck, Jessica; Cameron, David; Higgins, Ben; Pepper, Lisa; Ridley, Ellen; Sullivan, Emma; Carroll, Daniel J.
Abstract: The socioeconomic attainment gap in mathematics starts early and increases over time. This study aimed to examine why this gap exists. Four‐year‐olds from diverse backgrounds were randomly allocated to a brief intervention designed to improve executive functions ( N  = 87) or to an active control group ( N  = 88). The study was preregistered and followed CONSORT guidelines. Executive functions and mathematical skills were measured at baseline, 1 week, 3 months, 6 months, and 1 year posttraining. Executive functions mediated the relation between socioeconomic status and mathematical skills. Children improved over training, but this did not transfer to untrained executive functions or mathematics. Executive functions may explain socioeconomic attainment gaps, but cognitive training directly targeting executive functions is not an effective way to narrow this gap.